2000
DOI: 10.1038/sj.cdd.4400759
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 down-regulation causes autophagy in a caspase-independent manner in human leukemic HL60 cells

Abstract: To understand the roles of bcl-2 for the survival of leukemic cells, we constructed human leukemic HL60 transformant lines in which full length bcl-2 antisense message was conditionally expressed by a tetracycline-regulatable expression system. Cell growth was completely inhibited after antisense message induction and massive cell death was induced. Electron microscopic examinations show that cells died by autophagy, but not by apoptosis. The morphology and the function of mitochondria remained intact: neither… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
127
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 178 publications
(138 citation statements)
references
References 20 publications
10
127
0
1
Order By: Relevance
“…Moreover, the presence of LC3-positive vacuoles in relation to the expression and localization of beclin-1 and bcl-2 was compa-tible with the predicted model of bcl-2-mediated regulation of beclin-1-dependent autophagy. 37 Our data are in agreement with the observation of Saeki et al, 38 who reported an increase of basal autophagy in leukaemic cells after downregulation of bcl-2 expression. In a few cases, tumours with a low percentage of beclin-1-positive cells presented with a relative high proportion of LC-3-positive cells, which is suggestive of the activation of a beclin-1-independent autophagy pathway.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, the presence of LC3-positive vacuoles in relation to the expression and localization of beclin-1 and bcl-2 was compa-tible with the predicted model of bcl-2-mediated regulation of beclin-1-dependent autophagy. 37 Our data are in agreement with the observation of Saeki et al, 38 who reported an increase of basal autophagy in leukaemic cells after downregulation of bcl-2 expression. In a few cases, tumours with a low percentage of beclin-1-positive cells presented with a relative high proportion of LC-3-positive cells, which is suggestive of the activation of a beclin-1-independent autophagy pathway.…”
Section: Discussionsupporting
confidence: 93%
“…86 The accumulation of autophagy gene products during cell death, and their relationship with members of the Bcl-2 family, is a promising track to explore in order to obtain a better understanding of how autophagy is controlled during cell death. 68,87 The interaction between Beclin 1 and Bcl-2/Bcl-xL 88 is probably a key event in turning the accumulation of autophagosomes on or off. 68 Mitochondria play a central role in the execution of apoptosis by releasing apoptotic factors.…”
Section: Resultsmentioning
confidence: 99%
“…DNA damage or inhibition of protein kinases with staurosporine) induce necrosis when ATP supply is limited. 11 Downmodulation of the antiapoptotic protein Bcl-2 25 or upregulation of the proapoptotic Bcl-2 homolog BNIP3 26 can induce death accompanied by autophagic vacuolization. In mouse embryonic fibroblasts lacking the proapoptotic proteins Bax and Bak, alkylating DNA damage induces a necrotic type of cell death that relies on ATP depletion, 27 and etoposide induces an autophagic type of cell death dependent on autophagy proteins ATG5 and beclin, 28 while both types of damage induce apoptosis in Bax-or Bak-sufficient control cells.…”
Section: Inhibition/replacement Of Cell Death Typesmentioning
confidence: 99%